2008
DOI: 10.1063/1.2964635
|View full text |Cite
|
Sign up to set email alerts
|

Flow Analysis for Wormlike Micellar Solutions in an Axisymmetric Capillary Channel

Abstract: Flows of wormlike micellar solutions in an axisymmetric capillary channel were studied both numerically and experimentally. In the experimental study, velocity distribution measurements with a particle tracking velocimetry (PTV) were carried out using an aqueous solution of 0.03 mol/1 CTAB and 0.06 mol/1 NaSal as a test fluid. The velocity profile showed a plug-like shape and had infiection points where the velocity gradient rapidly changed. High shear rate regions near the channel walls spread with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 5 publications
(6 reference statements)
2
9
0
1
Order By: Relevance
“…These predictions of the molecular model presented so far are in agreement with recent experiments and predictions worked out by Yamamoto et al [23]. The flow curve for a micellar solution of CTAB/NaSal (cetyltrimethylammonium bromide with sodium salicylate) used by these authors is similar to that shown in Fig.…”
Section: Poiseuille's Flowsupporting
confidence: 89%
See 1 more Smart Citation
“…These predictions of the molecular model presented so far are in agreement with recent experiments and predictions worked out by Yamamoto et al [23]. The flow curve for a micellar solution of CTAB/NaSal (cetyltrimethylammonium bromide with sodium salicylate) used by these authors is similar to that shown in Fig.…”
Section: Poiseuille's Flowsupporting
confidence: 89%
“…Boundary conditions and temperature affect the velocity profiles, gradient-banding and modify the rheological behavior of the system [20][21][22]. In pressure-driven Poiseuille's flow, experiments on flow visualization show regions of turbidity [23], lying almost parallel next to the wall, growing toward the channel center with increasing wall shear rate. These layers can be associated with a secondary flow comprising velocity rolls [24].…”
Section: Introductionmentioning
confidence: 98%
“…The two regions are connected by an interfacial transition layer of characteristic width √ ı; which varies as the channel height changes. At the critical pressure drop, a jump in the volumetric flow rate or 'spurt' is predicted which has been observed in experiments [18,19]. To resolve the complex spatial structure of the velocity profile, including the interfacial layer between the two bands and the apparent slip layer at the wall, an adaptive domain decomposition spectral method has been formulated.…”
Section: Discussionmentioning
confidence: 98%
“…In pressure-driven flows of wormlike micellar solutions the underlying non-monotonic relationship between flow rate and pressure drop along a channel or pipe results in 'spurt phenomena' [17][18][19]. Beyond a critical pressure gradient the classical parabolic velocity profile expected for a Newtonian or Maxwell fluid becomes increasingly plug-like with shear bands forming in the regions of high shear stress near the walls.…”
Section: Introductionmentioning
confidence: 98%
“…Shear-banded profile was reported in the flow of wormlike micelle solution in slit channel (Fielding and Wilson 2010;Marín-Santibáñez et al 2009;Masselon et al 2008;Yamamoto et al 2008). In the wide channel, this fluid showed change of flow profile from parabolic shape (Poiseuille-like flow) to plug flow with lower viscosity bands closed to the channel wall (Masselon et al 2008).…”
Section: Steady State Flow Behavior Of Concentrated Alumina Suspensionmentioning
confidence: 95%